(untitled) (International Journal of Ayurveda and Pharma Research, 2016)
The health of an individual depends solely on his diet and life style. Diet plays very important role in Parikartika which is evident by references. The earliest reference of Parikartika is available from Sushrutha Samhitha (1500 B.C). Description about Parikartika is also available in all Bruhatrayees and later classics. Parikartika is referred in Brihatrayees not as an independent disease but as a complication of Bastikarma and Virechana (vyapath). Fissure-in-ano is very commonly encountered in current day to day practice. About 30-40% of the population suffer from proctologic pathologies at least once in their life. Anal fissure comprises of 10-15% of anorectal disorders and is characterized by excruciating pain during and after defecation, bleeding per anus with spasm of anal sphincter. Parikartika is characterized by Kartanavat and Chedanavat shoola in Guda. Similarly Fissure-in-ano is also characterized by sharp cutting pain in anal region. In Parikartika, Teevra shoola, Piccha-asra are seen, similarly severe pain and slimy blood discharge are seen in Fissure-in-ano. Parikartika is treated with internal medications and local applications formulated by using Madhura, Sheeta, Snigdha dravyas. Local therapies in the form of Anuvasana basti, Picchabasti, Madhura, Kashaya dravya Siddha basti taila poorana, Lepa, Pichu dharana are given prime importance in the management. Sentinel Piles is a sequel of chronic fissure-in-ano. In Ayurvedic text no specific description available as a sequel of Parikartika but lots of references available with help of that we can compare Sentinel Piles with Ayurvedic pathogenesis. In Ayurvedic text information available on Shushkarsh, Bahyarsh, Vataj, Janmottar-kalaj Arsha can be correlated with Sentinel Piles.